Fungal burden of bread raw material and settled dust from Portuguese bakeries - Viegas, Carla (2018)
The Food and Agriculture Organization estimated that approximately 25% of the cereals produced in the world are contaminated with mycotoxins. Crops protection includes the use of fungicides such as triazoles, also used in clinical settings. In this study, we aimed at assessing fungal contamination and resistant species of bread raw material and also settled dust from 5 Portuguese bakeries. Twenty-six samples of bread raw material and one settled dust sample from each bakery were assessed. 4.4 g of raw material/settled dust was weighted and added 40 ml of distilled water for extraction (20´at 200 rpm). 150 uL of this suspension was spread onto malt extract agar (2%) with chloramphenicol (0.05 g/L) (MEA), in dichloran glycerol (DG18) and onto screening media to detect azole-resistant fungal isolates. None of the settled dust analyzed presented fungal growth. However, in two bakeries fungal growth was isolated in 1 flour sample (one with Aspergillus section Circumdati, another with A. section Versicolores). In a third bakery, 3 different flour samples showed fungal growth (2 with A. section Versicolores, another with A. section Versicolores, Mucor sp. and Penicillium sp.). In a fourth bakery, fungal isolates were identified in 4 samples (1 with Penicillium sp., 2 with A. section Candidi, another with Syncephalastrum racemosum). Additionally, the growth of resistant fungi in 1 flour sample was observed in 2 bakeries (1 with Mucor sp. resistant to voriconazole, another with Chrysosporium sp. resistant to itraconazole). Results demonstrate the importance of a detailed characterization of fungal burden since toxigenic and resistant species were isolated. The results claim attention for the possible presence of mycotoxins in bread as they resist to high temperatures. Azole-resistant species detected may have originated due to the use of triazole fungicides in cereals crops contributing to the development of multiresistant fungal populations.